2010
DOI: 10.1037/a0017675
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for deficits in reward responsivity in antisocial youth with callous-unemotional traits.

Abstract: This study investigated reward responsivity in youth with high levels of callous-unemotional (CU) traits using a cross-sectional design. Whereas deficits in responding to punishment cues are well established in youth with CU traits, it is unclear whether responsivity to rewarding stimuli is impaired as well. Participants were 148 predominantly Caucasian, adjudicated adolescents between the ages of 11 and 17 (M = 15.1, SD = 1.4) who completed the Balloon Analogue Risk Task as part of a larger battery investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 72 publications
4
39
1
1
Order By: Relevance
“…In line with this idea, emergent research using the Balloon Analogue Risk Task (BART; Lejuez et al, 2002) suggests that in incarcerated samples, youth high on CU traits demonstrate a decreased reward orientation relative to youths low on CU traits (Marini & Stickle, 2010). Further, the decreased punishment responsivity characteristic of youth high on CU traits is argued to play a minor role in decisions to act out (e.g., Blair, 2010), so that lack of response to punishment is unlikely to fully account for their decidedly antisocial decisions.…”
Section: Callous-unemotional Traits and Risk-takingmentioning
confidence: 93%
See 3 more Smart Citations
“…In line with this idea, emergent research using the Balloon Analogue Risk Task (BART; Lejuez et al, 2002) suggests that in incarcerated samples, youth high on CU traits demonstrate a decreased reward orientation relative to youths low on CU traits (Marini & Stickle, 2010). Further, the decreased punishment responsivity characteristic of youth high on CU traits is argued to play a minor role in decisions to act out (e.g., Blair, 2010), so that lack of response to punishment is unlikely to fully account for their decidedly antisocial decisions.…”
Section: Callous-unemotional Traits and Risk-takingmentioning
confidence: 93%
“…Yet, other research has found high psychopathy adults within community samples are more successful in card playing relative to low psychopathy adults, but not more risky (Belmore & Quinsey, 1994). Likewise, studies of jailed adults (Swogger, 2010) and adolescents (Marini & Stickle, 2010) failed to find an association between psychopathic traits and behavioral risk-taking. These findings suggest that individuals high on CU may be more successful in their risk-taking, if not more risky overall, relative to other individuals.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…However, Marini and Stickle (2010) examined sensitivity to reward in children with CU traits and concluded that these traits also significantly predated a lowered sensitivity to reinforcement. They propose that instead of a one-sided deficit, discrepancies exist in both sensitivity to reward and punishment.…”
Section: Theories Of Maladaptive Responses To Behavioral Contingenciesmentioning
confidence: 99%